Antegrade transseptal transcatheter aortic valve replacement: Back to the future?. Issue 5 (30th April 2020) - Misumida, Naoki; Anderson, Jason H.; Greason, Kevin L.; Rihal, Charanjit S.
Abstract: Antegrade transseptal approach was utilized in the first human case of transcatheter aortic valve replacement (TAVR) and in the early phase of TAVR. Various challenges with the antegrade transseptal approach including procedural complexity, need for atrial septal crossing, and potential for injury to the mitral valve apparatus led it to being supplanted by other approaches. These challenges have now largely been mitigated as structural interventionalists routinely perform left atrial procedures. We report a case of antegrade transseptal TAVR using a large bore sheath placed in the mid left ventricle across the mitral orifice to protect the mitral valve apparatus and facilitate valve deployment. An 84‐year‐old man with heart failure symptoms was seen for severe aortic stenosis. The severity of peripheral arterial disease precluded femoral, axillary, carotid, or transcaval routes. After transseptal puncture and creation of an arteriovenous rail, a long 26‐Fr sheath was advanced from the right femoral vein transseptally over the arteriovenous rail, past the mitral valve inflow to the mid left ventricular cavity. The sheath provided a stable platform with stable intraprocedure hemodynamics. Balloon valvuloplasty was performed in an antegrade manner, after which a 29‐mm SAPIEN S3 prosthesis was advanced into the aortic valve position and deployed under rapid pacing. We observed no injury to the mitral leaflets or subvalvular apparatus after the procedure. The antegrade transseptal approach should be revisited as an option for patients at high surgical risk with no other suitable access site. The use of a large bore sheath facilitates this approach.